International Cooperation, Competition Authorities and Transnational Networks - Mateusz Błachucki (Routledge, 2024)
This book presents a comprehensive study of the emergence, functioning and evolution of international cooperation among competition authorities. It presents an in-depth look at network cooperation taking place within international organisations, as well as networks based on binding international agreements and various informal networks, among others. It further identifies and analyses the forms of international cooperation among national competition authorities (NCAs) that are taking place within transnational competition networks. The book classifies these forms of cooperation by grouping them into three stages – soft, developed and enhanced cooperation – discussing each in detail. It thus reflects the evolution of the international cooperation process and provides insights as to its possible development. This work will be of interest to researchers, academics and advanced students in the fields of competition law, public administration, international relations and those interested in international competition law and its contribution to global public governance.
Keywords: 340; Competition law; Competition authorities; International cooperation; Transnational networks; EU law; Administrative law